2020
DOI: 10.1002/chem.202000417
|View full text |Cite
|
Sign up to set email alerts
|

Stapled Peptides as HIF‐1α/p300 Inhibitors: Helicity Enhancement in the Bound State Increases Inhibitory Potency

Abstract: Protein–protein interactions (PPIs) control virtually all cellular processes and have thus emerged as potential targets for development of molecular therapeutics. Peptide‐based inhibitors of PPIs are attractive given that they offer recognition potency and selectivity features that are ideal for function, yet, they do not predominantly populate the bioactive conformation, frequently suffer from poor cellular uptake and are easily degraded, for example, by proteases. The constraint of peptides in a bioactive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 97 publications
0
18
0
Order By: Relevance
“…MD simulations indicated that both the constrained and unconstrained peptides showed greater helical character in the bound state when compared to the unbound peptides, with a more dramatic increase observed for the DBM stapled peptide. Thus, the staple-induced affinity enhancement was proposed to occur as a result of stabilizing the bound state of the peptide in complex with p300 46 and was supported by experimental CD difference experiments. In a similar vein, Grossmann and co-workers also observed that changes in the behaviour of bound state as a consequence of introducing a constraint are important for interaction of Exoenzyme S (Exo S) derived peptides with 14–3–3 protein although in this case, increased affinity was attributed to increased dynamics in the peptide-receptor complex.…”
Section: Enhancing Protein Binding Affinitymentioning
confidence: 71%
See 1 more Smart Citation
“…MD simulations indicated that both the constrained and unconstrained peptides showed greater helical character in the bound state when compared to the unbound peptides, with a more dramatic increase observed for the DBM stapled peptide. Thus, the staple-induced affinity enhancement was proposed to occur as a result of stabilizing the bound state of the peptide in complex with p300 46 and was supported by experimental CD difference experiments. In a similar vein, Grossmann and co-workers also observed that changes in the behaviour of bound state as a consequence of introducing a constraint are important for interaction of Exoenzyme S (Exo S) derived peptides with 14–3–3 protein although in this case, increased affinity was attributed to increased dynamics in the peptide-receptor complex.…”
Section: Enhancing Protein Binding Affinitymentioning
confidence: 71%
“…Hetherington et al prepared and investigated a series of constrained peptides to target HIF-1α/p300; 46 a PPI which regulates oxygen levels in cells and is often hijacked by cancer to supply growing tumours with oxygen. 47–49 Here, the peptides were constrained through reaction of dibromomaleimide with i and i + 4 Cys residues.…”
Section: Enhancing Protein Binding Affinitymentioning
confidence: 99%
“…In this context, different peptide and phage display libraries as well as synthetic HIF-1α (aa 812–826)-derived peptides were examined for their binding to p300 and their adopted conformation when bound to the CH1 domain. Designed synthetic and constrained peptides that were able to adopt α-helical conformation in their bound state to p300 were more efficient competitors of HIF-1α C-TAD and may represent lead compounds for the development of peptidomimetic HIF-1α/p300 inhibitors (see also below) [ 126 , 127 ].…”
Section: Hif Inhibitors As Therapeuticsmentioning
confidence: 99%
“…By focusing on the largest helical segment, and using a dibromomaleimide stapling strategy, a competitive binder of the HIF‐1α peptide with increased helicity in the bound state was reported (Figure 2A). [ 54 ]…”
Section: Section 1: Defining the Primary Sequencementioning
confidence: 99%
“…By focusing on the largest helical segment, and using a dibromomaleimide stapling strategy, a competitive binder of the HIF-1α peptide with increased helicity in the bound state was reported ( Figure 2A). [54] Nonhelical stapled peptides have also been developed in recent papers targeting nuclear PPIs. Wiedmann et al [55] used peptides based on an HNF1β NLS sequence developed in the 1990s by Lin et al [59] and "double click" CuACC staple chemistry, [60,61,62] to produce a series of constrained extended stapled peptides ( Figure 2B).…”
Section: Natural Peptide Interaction Sequencesmentioning
confidence: 99%